2001
DOI: 10.1105/tpc.13.5.1095
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Plasma Membrane ATP Binding Cassette–Type Transporter Is Involved in Antifungal Terpenoid Secretion

Abstract: ATP binding cassette (ABC) transporters, which are found in all species, are known mainly for their ability to confer drug resistance. To date, most of the ABC transporters characterized in plants have been localized in the vacuolar membrane and are considered to be involved in the intracellular sequestration of cytotoxins. Working on the assumption that certain ABC transporters might be involved in defense metabolite secretion and their expression might be regulated by the concentration of these metabolites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(103 citation statements)
references
References 56 publications
1
102
0
Order By: Relevance
“…749 and 750), that implies that the diffusion of xenobiotics through phospholipid bilayers in intact cells is normally negligible. It is now clear that transporters enhance (and are probably required for) the transmembrane transport even of hydrophobic molecules such as alkanes, 13161321 terpenoids, 1319,1322,1323 long-chain, 13241328 and short-chain 13291332 fatty acids, and even CO 2 . 1333,1334 This may imply a significantly enhanced role for transporter engineering in whole cell biocatalysis.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…749 and 750), that implies that the diffusion of xenobiotics through phospholipid bilayers in intact cells is normally negligible. It is now clear that transporters enhance (and are probably required for) the transmembrane transport even of hydrophobic molecules such as alkanes, 13161321 terpenoids, 1319,1322,1323 long-chain, 13241328 and short-chain 13291332 fatty acids, and even CO 2 . 1333,1334 This may imply a significantly enhanced role for transporter engineering in whole cell biocatalysis.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…While other mechanisms are also possible (Dikicioglu et al, 2014), the ABC transporter (Sá-Correia et al, 2009) Pdr18 (Teixeira et al, 2012) and the glyceroaquaporin Fps1 (Teixeira et al, 2009) have properties consistent with such a role as ethanol transporters in yeast, a fact of considerable biotechnological relevance (Dunlop et al, 2011). In the context of biofuels production (and ethanol is a biofuel), and based on similar strategies of toxicity resistance to the one that we exploited earlier (Lanthaler et al, 2011), we now also know them for a variety of other rather lipophilic substances such as alkanes (Tsukagoshi and Aono, 2000; Fernandes et al, 2003; Ankarloo et al, 2010; Chen et al, 2013; Doshi et al, 2013; Foo and Leong, 2013; Ling et al, 2013; Nishida et al, 2013), arenes (Kieboom et al, 1998b), terpenoids (Jasiński et al, 2001; Yazaki, 2006; Foo and Leong, 2013), long-chain fatty acids (Wu et al, 2006a,b; Khnykin et al, 2011; Lin and Khnykin, 2014; Villalba and Alvarez, 2014), short-chain fatty acids (Gimenez et al, 2003; Islam et al, 2008; Moschen et al, 2012; Sá-Pessoa et al, 2013), etc. These are all substances for which bilayer lipoidal diffusion was “once widely assumed” (and presumably still is in some quarters).…”
Section: Intellectual Challenges Around Bilayer Lipoidal Permeabilitymentioning
confidence: 99%
“…All PDRs characterized so far are plasma membrane transporters (Kang et al, 2011), and the first to be identified in plants, the Spirodella polyrhiza SpTUR2 and the Nicotiana plumbaginifolia NpPDR1, mediate the transport of terpenes (Jasinski et al, 2001; van den Brule et al, 2002). SpTUR2 expression in Arabidopsis confers resistance to the diterpenoid sclareol, as does the Arabidopsis AtABCG40 (Campbell et al, 2003) later shown to function in cellular uptake of the sesquiterpenoid ABA (Kang et al, 2010).…”
Section: Abc Transportersmentioning
confidence: 99%
“…Another PDR transporter, AtABCG36, is involved in cadmium (Kim et al, 2007) and sodium toxicity (Kim et al, 2010) resistance. Following the findings that NpPDR1 secretes antifungal terpenoids (Jasinski et al, 2001) and contributes to basal plant defense (Stukkens et al, 2005), AtABCG36 was identified as a key factor in the resistance to fungal and bacterial pathogens (Kobae et al, 2006; Stein et al, 2006; Underwood and Somerville, 2013; Xin et al, 2013). Moreover, both AtABCG36 and AtABCG37 excrete a range of synthetic auxins, including 2,4-D, and indole-3-butyric acid (IBA), the natural IAA precursor (Ito and Gray, 2006; Strader and Bartel, 2009; Ruzicka et al, 2010).…”
Section: Abc Transportersmentioning
confidence: 99%